(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2011)
The study examined tourist experiences on IRCTC by conducting qualitative content analysis of 100 online reviews which were divided into Pre-Trip, Entrance, Payment, and Post-Visit stages. The study showed both positive aspects of digital accessibility and affordability alongside negative aspects regarding ticket availability and station infrastructure alongside payment reliability and service consistency. The analysis identified essential improvement zones for digital performance alongside better customer assistance and standardized services which would strengthen overall passenger satisfaction. The study examined IRCTC as well as Tourist Journey and Railway Tourism through Online Booking and Qualitative Research to evaluate Customer Experience and Service Quality and Ticket Availability and Qualitative Tourism Research with Digital Payments and Travel Satisfaction and Tourism Experience in Indian Tourism. The research stated that how IRCTC excels at digital accessibility and affordable service but points out ticket availability issues along with station infrastructure problems and payment reliability concerns and service consistency problems. The satisfaction of passengers can be improved by implementing digital improvements and enhanced customer support with standardized services to address current gaps. Future investigations must combine quantitative research methods with international railway tourism frameworks to establish strategic service development plans.